Analysis of the Effect of Public Infrastructure on the Economy in South Sumatra Province - Sari, Arta Mevia; Sunoto, Sunoto (Indonesian Journal of Business Analytics, 2023)
The purpose of this study is to analyze how much influence Road Infrastructure, Water and Electricity, on GRDP in South Sumatra Province.  The data used in this study is secondary data which includes GRDP data at constant 2010 prices, road length according to good road conditions, water data using the amount of water supplied, and electricity data using the distribution of electricity sold in South Sumatra Province from 2018-2022. The data obtained will be analyzed through panel data regression. The results showed that road infrastructure development has a positive and significant impact on Gross Regional Domestic Product (GRDP), while water infrastructure has a positive but insignificant impact on GRDP. In addition, electricity infrastructure also has a positive and significant impact on GRDP. The results also show that the road and electricity variables jointly affect the GRDP variable in South Sumatra Province in 2018-2022.